0665 Bilateral Hypoglossal Nerve Stimulation for Treatment of Obstructive Sleep Apnea. (27th May 2020) - Eastwood, P R; Barnes, M; MacKay, S G; Wheatley, J R; Lewis, R; Campbell, M C; Jones, A C; Palme, C E; Petelle, B; Meslier, N; Bertolus, C; Denoncin, K; et al.
Abstract: Introduction: Hypoglossal Nerve Stimulation (HGNS) decreases obstructive sleep apnea (OSA) severity by contracting the tongue and decreasing upper airway collapsibility. This study assessed the safety and effectiveness of a new implantable device that delivers bilateral HGNS: the Genio™ system. Methods: The BLAST OSA study (BiLAteral Hypoglossal Nerve Stimulation for Treatment of Obstructive Sleep Apnea), was a prospective, open-label, non-randomized, single arm treatment study conducted at eight centres in three countries (Australia, France, UK). Primary outcomes were the incidence of device-related Serious Adverse Events (SAEs) and change in the Apnea-Hypopnea Index (AHI). The secondary outcome was change in the 4% Oxygen Desaturation Index (ODI). Additional outcomes included measures of sleepiness, quality of life, snoring, and device use. Participants were eligible if: 21-75 years old; BMI ≤ 32 kg/m 2 ; obstructive AHI 20-60 events/hr and combined central and mixed AHI < 10 events/hr; no positional OSA; no Complete Concentric Collapse of the soft palate during Drug Induced Sleep Endoscopy; and failed to tolerate or accept Positive Airway Pressure treatments. Results: 27 participants were implanted (63% male, aged 55.9±12.0 years, BMI 27.4±3.0 kg/m 2 ). 22 completed the protocol. At 6 months, AHI decreased from 23.7±12.2 to 12.9±10.1 events/hr [p<0.001]; and ODI decreased from 19.1±11.2 to 9.8±6.9 events/hr [p<0.001]. Daytime sleepiness (ESS, p=0.011) and sleep-related quality of life (FOSQ-10, p=0.016) both significantly improved. 91% of participants reported using their device >5 days per week, and 77% used it >5 hours per night. The number of bed partners reporting disruptive snoring decreased from 96% to 35%. No device-related SAE occurred. Conclusion: In a targeted population of individuals with moderate-to-severe OSA, the Genio system reduced OSA severity and sleepiness, improved quality of life, and was associated with high adherence and an acceptable safety profile. Support: This study trial was funded by Nyxoah S.A. This trial was registered with ClinicalTrials.gov, number NCT03048604.